A linguagem fotográfica como recurso pedagógico visual e reveladora da cultura extrativista - Vasconcelos, Aurelice (2019)
This work presents an experience of pedagogical workshops for the photographs production and image reading. The theme developed by this study was the photographic production by the students of the Rural Municipal School of Primary Education of the Extractivist Reserve of Cazumbá-Iracema, in the Amazonian Forest of State of Acre, in Brazil. The objective was the use of photography as visual production, wakening the critical perception of the world in which they live and of their culture. The use of pedagogical workshop as methodology allowed the students to reveal the extractive way of life of the community